From which Ocotea diospyrifolia trees does Alouatta caraya (Primates, Atelidae) eat fruits? - Bravo, Susana Patricia (2012)
Ecological and morphological traits of fruiting trees, such as spatial distribution (Levey et al. 1984), crop size (Howe & vande Kerckhove 1981, Korine et al. 2000, Leighton 1993, Murray 1987), local availability of fruit (Sargent 1990), seed size or pulp/seed mass ratio (Julliot 1996a, Leighton 1993, McConkey et al. 2002, Russo 2003, Stevenson et al. 2005) and nutritional value and concentration of secondary compounds (Leighton 1993, Milton 1980, Sallabanks 1993), influence fruit preference in animals. In general, frugivores maximize energy intake by consuming ripe fruit with smaller seeds, higher pulp/seed ratio, bigger crop size, more nutritional fruits or fruits with fewer secondary compounds (Howe & vande Kerckhove 1981, Julliot 1996a, Korine et al. 2000, Leighton 1993, Milton 1980, Murray 1987, Russo 2003, Stevenson et al. 2005). Copyright © 2012 Cambridge University Press.